A randomized, controlled, double-blind, crossover trial of triheptanoin in alternating hemiplegia of childhood - Elodie Hainque; Samantha Caillet; Sandrine Leroy; Constance Flamand-Roze; Isaac Adanyeguh; Fanny Charbonnier-Beaupel; Maryvonne Retail; Benjamin Le Toullec; Mariana Atencio; Sophie Rivaud-Péchoux; Vanessa Brochard; Florence Habarou; et al. (Orphanet Journal of Rare Diseases, 2017)
Abstract Background Based on the hypothesis of a brain energy deficit, we investigated the safety and efficacy of triheptanoin on paroxysmal episodes in patients with alternating hemiplegia of childhood due to ATP1A3 mutations. Methods We conducted a randomized, double-blind, placebo-controlled crossover study of triheptanoin, at a target dose corresponding to 30% of daily calorie intake, in ten patients with alternating hemiplegia of childhood due to ATP1A3 mutations. Each treatment period consisted of a 12-week fixed-dose phase, separated by a 4-week washout period. The primary outcome was the total number of paroxysmal events. Secondary outcomes included the number of paroxysmal motor-epileptic events; a composite score taking into account the number, severity and duration of paroxysmal events; interictal neurological manifestations; the clinical global impression-improvement scale (CGI-I); and safety parameters. The paired non-parametric Wilcoxon test was used to analyze treatment effects. Results In an intention-to-treat analysis, triheptanoin failed to reduce the total number of paroxysmal events (p = 0.646), including motor-epileptic events (p = 0.585), or the composite score (p = 0.059). CGI-I score did not differ between triheptanoin and placebo periods. Triheptanoin was well tolerated. Conclusions Triheptanoin does not prevent paroxysmal events in Alternating hemiplegia of childhood. We show the feasibility of a randomized placebo-controlled trial in this setting. Trial registration The study has been registered with clinicaltrials.gov ( NCT002408354 ) the 03/24/2015.